PWE-067 Does Endocuff-vision Improve Adenoma Detection. (9th June 2014) - Tsiamoulos, ZP; Patel, K; Elliott, T; Misra, R; Thomas-Gibson, S; Fraser, C; Haycock, A; Saunders, BP
Abstract : Introduction: Although colonoscopy is considered the optimal procedure for bowel cancer screening, it remains an imperfect tool for cancer prevention, due to missed adenomas and early cancers. Optimal imaging modalities, innovative scopes and accessories (cap-assisted colonoscopy) have attempted to decrease the adenoma miss rate. Adenoma detection rates (ADR) have been shown to be a key performance indicator Methods: Endocuff-vision is a simple accessory mounted at the end of the scope with a proximal row of 6mm length soft plastic, finger-like projections. During scope insertion, these projections invert towards the shaft of the tube and during withdrawal they evert to hold back the colonic folds augmenting the forward endoscopic views. ADRs were recorded and evaluated for screening colonoscopy procedures before and after introduction of Endocuff-vision. Results: To date, four screening endoscopists (BPS, STG, CF, AH) have used the Endocuff-vision as part of a clinical evaluation process form August 2013 until November 2013. From our local Bowel Cancer Screening Program database, the figures of caecal intubation rate (CIR) and the ADRs of the screening endoscopists during April 2013 to July 2013 before Endo-cuff were retrieved: BPS: CIR-100%/ADR-62.72%, STG: CIR-95.84%/ADR-40.03%, CF: CIR-93%/ADR-36.76%, AH: CIR-96.25%/ADR- 55.35%. Prior to the introduction of the Endocuff-vision, the cumulative CIR was 96.27% and ADR was calculated to be 48.71% . The total number of procedures where Endocuff-vision has been mounted was in 30 occasions (BPS-10, STG-11, CF-3, AH-6) with similar CIR rates but increased cumulative ADR of 65.5%. On 3 patients the Endocuff-vision was electively removed from the scope due to insertion difficulties through fixed sigmoid colonic segments secondary to severe diverticular disease. There were no adverse events reported during the trial evaluation period. Conclusion: In this small pilot study, use of the Endocuff appeared to improve the ADR by 17%. There were no complications from the use of the cuff although it was electively removed in 3 cases with severe sigmoid colon diverticulosis. Further randomised evaluation of this simple novel device is warranted. Disclosure of Interest: None Declared.